THEORETICAL FOUNDATIONS OF FITNESS PROGRAMS FOR THE ELDERLY (Physical Culture and Sport: Scientific Perspective, 2024)
The aim of our research is to theoretically substantiate the main directions and principles of implementing fitness programs for the elderly. The research employs theoretical methods, including the analysis of scientific literature, data systematization, and conceptual analysis. Scientific publications on fitness for the elderly are studied, along with an analysis of previous research findings. A comparative analysis of various fitness programs for the elderly is applied to determine the most effective approaches and principles. Contemporary physical activity for first-age women encompasses diverse realms such as dance fitness, strength training, and bodybuilding, improving both the functional state of the body and body weight correction. Over 100 modern fitness programs are classified into categories like aerobic endurance, strength endurance, figure correction, and coordination abilities. Researchers emphasize the importance of individualization, safety, progression, variety, adaptation, and support in developing and implementing fitness programs for the target audience. The principles of individualization, safety, progression, variety, adaptation, and support are identified as crucial for achieving physical and psychological well-being in mature age. Conclusions: Today, health and an active lifestyle are a priority, making the theoretical foundations of fitness programs for the elderly relevant and significant. Individualization, safety, and gradual progression of training, promoting health, social integration, and psychological comfort are key aspects. Diverse programs catering to individual needs underscore the relevance of fitness for the elderly. Theoretical approaches contribute to the creation of flexible and effective strategies to support health and quality of life.
Keywords: health and recreational physical activity; fitness; elderly